Eating in the absence of hunger in young children is related to brain reward network hyperactivity and reduced functional connectivity in executive control networks. Issue 6 (18th January 2019) - Shapiro, Allison L. B.; Johnson, Susan L.; Sutton, Brianne; Legget, Kristina T.; Dabelea, Dana; Tregellas, Jason R.
Summary: Background: Recent work has implicated disinhibited eating behaviours (DEB) as a potential pathway toward obesity development in children. However, the underlying neurobiology of disinhibited eating behaviours in young, healthy weight children, prior to obesity development, remains unknown. Objectives: This study tested the relationship between DEB and intrinsic neuronal activity and connectivity in young children without obesity. Methods: Brain networks implicated in overeating including reward, salience and executive control networks, and the default mode network were investigated. DEB was measured by the eating in the absence of hunger (EAH) paradigm with postlunch kilocalories consumed from highly palatable foods (EAH kcal) used as the predictor. Intrinsic neuronal activity within and connectivity between specified networks were measured via resting‐state functional magnetic resonance imaging. Eighteen typically developing children (mean age = 5.8 years) were included. Results: EAH kcal was positively associated with activity of the nucleus accumbens, a major reward network hub ( P  < 0.05, corrected). EAH kcal was negatively associated with intrinsic prefrontal cortex connectivity to the striatum ( P  < 0.01, corrected). Conclusions: These results suggest that neural aspects of DEB are detectable in young children without obesity, providing a potential tool to better understand the development of obesity in this population.